2022
DOI: 10.1037/pro0000417
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions on the front lines: A roadmap for the development of a behavioral treatment program to mitigate the mental health burden faced by COVID-19 survivors.

Abstract: Survivors of prolonged hospitalization due to coronavirus disease 2019 (COVID-19) are at risk for psychiatric symptoms that can interfere with rehabilitation and functional outcomes. We developed an hishek Jaywant,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…With that, the present study presents similarities with the findings in the literature that observed improvements in the PHQ-9 and GAD-7 scores [34,47]. Considering the evidence that points to the need for care for these individuals who have post-COVID symptoms [9,[47][48][49], a unique look at the population after the COVID-19 pandemic becomes relevant so that effective techniques can be developed for the treatment of all the symptoms of this syndrome. Prolonged symptoms affect individuals' quality of life and well-being [50].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…With that, the present study presents similarities with the findings in the literature that observed improvements in the PHQ-9 and GAD-7 scores [34,47]. Considering the evidence that points to the need for care for these individuals who have post-COVID symptoms [9,[47][48][49], a unique look at the population after the COVID-19 pandemic becomes relevant so that effective techniques can be developed for the treatment of all the symptoms of this syndrome. Prolonged symptoms affect individuals' quality of life and well-being [50].…”
Section: Discussionsupporting
confidence: 84%
“…The scientific literature indicates that psychoeducation added to physical activities and a multi-professional approach can positively influence psychological aspects, such as a well-being decrease in anxiety and depressive symptoms, and contribute to the treatment and prevention of depression, anxiety, and post-traumatic stress [23,30]. Some similar practices have already shown positive results, reducing the impacts caused by the COVID-19 pandemic and other psychiatric conditions [9,10,31]. Another recent study from our research group showed similar results in approaches with concurrent exercise and dietary reeducation in overweight or obese middle-aged females [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical staff consisting of clinical psychologists and psychology postdoctoral fellows delivered a course of up to 14 virtual, evidence-based psychotherapy sessions to patients who met criteria for clinically significant anxiety or depression. This cognitive-behavioral treatment (CBT) program integrated psychoeducation, cognitive restructuring, mindfulness, acceptance and exposure-based techniques described in detail elsewhere [ 10 ].…”
mentioning
confidence: 99%